Medicolegal Evaluation of Post-Traumatic Cognitive Impairments - Aydoğdu, Halil İlhan; Biçen, Emin; Atacan, Sibel Çağlar; Falihi, Afrodit (The Bulletin of Legal Medicine, 2022)
Objective: Head injuries and traumatic brain injury are a serious public health problem impacting It is well-known that each year, 55 million people are exposed to traumatic brain injury. The identification of head traumas, Traumatic Brain Injury, and Post-Traumatic Cognitive Impairment in respect of clinical forensic medicine applications are important in many judicial cases, primarily the claim that a disability is due to trauma.Material and Methods: The files of the patients who were referred for disability assessment between January 01, 2019 and December 31, 2019, and who were found to have suffered head trauma at the time of the incident, were retrospectively reviewed.Results: The ages of patients ranged between 14 and 78 years. The mean age was 39.8 ± 14.43, and the median age was 39. 109 (81.3%) of them were male and 25 (18.7) were female. As a result of the examination, imaging tests and neurocognitive test results for the disability assessment of the patients, 87 (64.9%) of them had organic brain damage causing significant cognitive damage. Post-traumatic stress disorder in 5 (3.7%) patients and other trauma-related sequelae (craniectomy defect, epilepsy, hearing or vision loss, etc.) were detected in 8 (6%) patients. WMS-I and WMS-II scores of the patients were found to be significantly lower in the Post-Traumatic Cognitive Impairment group (P=0.001). Moreover, the test results were determined to be significantly lower in WMS-IV (logical memory) tests (P=0.001).Conclusion: The diagnosis of Post-Traumatic Cognitive Impairment can be made through multidisciplinary clinical examination, radiological imaging, and neurocognitive tests.
Keywords: Cognitive Impairment; Head Trauma; Brain Damage; Neurocognitive test